2020
DOI: 10.51791/njap.v44i5.1297
|View full text |Cite
|
Sign up to set email alerts
|

Determination of proximate and phytochemical composition of African locust bean (Parkia biglobosa) forage

Abstract: Browse plants is one of the cheapest sources of feed for ruminants and other farm animals. The leaf of African locust bean (Parkia biglobosa), a tree belonging to the family leguminoceae was studied. The Locust bean foliage (LBF) was evaluated for the proximate and antinutritional factors. The proximate analysis showed that LBF had high crude protein (16.23%), dry matter DM (90.05%), crude fibre CF (21.36%), low fats (0.68%), ash (6.11) and soluble carbohydrate (55.62%). Anti–nutrients contents included oxalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Results of proximate analysis shown in Table 1 indicated that AYB used for this study, Figure 1 is a promising plant and has sufficient nutrients to meet the nutrient requirements of rabbits. The low moisture content of (7.04) favored the storage of AYB since high moisture content hastens spoilage of feedstuff and enhance microbial growth [18].…”
Section: Discussionmentioning
confidence: 99%
“…Results of proximate analysis shown in Table 1 indicated that AYB used for this study, Figure 1 is a promising plant and has sufficient nutrients to meet the nutrient requirements of rabbits. The low moisture content of (7.04) favored the storage of AYB since high moisture content hastens spoilage of feedstuff and enhance microbial growth [18].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonols, Flavonoids (Catechin, Quercetin, Epicatechin) Minerals: Calcium, Potassium, Magnesium, Sodium, Phenolic acids, and Tannins. Antioxidants and galactomannans play a vital part in defending cells against free radicals, which may also contribute to heart disease, cancer, and other disorders, according to the facts that surround locust beans and their structure [7]. Second, there are flavonoids, which have several medical advantages, including anticancer, antioxidant, anti-inflammatory, and antiviral characteristics [45].…”
Section: Locust Beans Components and Their Promising Protective Rolementioning
confidence: 99%
“…According to the result described by Lobo et al (2010) [50], the ferric-reducing antioxidant power (FRAP) results, the pulp has a significant amount of ferric-reducing ability (14.08 mg/g). This shows that the sample might serve as a reducing agent by neutralizing free radicals and giving them an electron, which would reduce their ability to cause adverse effects [7], [8]. In addition to locust bean germ which contains gallic acid a naturally occurring phenolic substance with known antioxidant properties [50].…”
Section: Locust Beans Components and Their Promising Protective Rolementioning
confidence: 99%
See 1 more Smart Citation
“…According to Afolayan et al (2017) browse plants are one of the cheapest sources of feed for ruminants and pseudo -ruminants. Shrubs and tree leaves are important feed resources in the diet of grazing animals (Ajiji et al, 2013).…”
Section: Introductionmentioning
confidence: 99%